Parallel Processing and Applied Mathematics : 13th International Conference, PPAM 2019, Bialystok, Poland, September 8-11, 2019, Revised Selected Papers.: 13th International Conference, PPAM 2019, Bialystok, Poland, September 8-11, 2019, Revised Selected Papers. Part I (2020) - Unknown
No abstract available